Mechanism design for demand response programs with social incentives implemented via multiagent systems (2018)
Abstract: Most demand management approaches with non-mandatory policies assume full users' cooperation, which may not be the case given users' beliefs, needs and preferences. The present project proposes a multiagent system approach, in which users are characterized by their preferences in regard to electric energy consumption, their flexibility to change these preferences, and by the subjective valuation given to the electric energy. Preferences may be unique for each electric device, and subjective valuation is assumed much higher than electricity cost, in order to capture properly the behavior of domestic users reported in the literature, which is known to be highly inelastic and inflexible. Using this model, the demand management potential is assessed with a mechanism implementation that involves financial and social incentives that aim to modify electricity consumption during a certain period. Financial incentives are expressed as a compensation given to those users whom act according to the demand management signal generated by the planner for a specific consumption period. In order to be effective, these incentives must guarantee to the user a higher profit than the one obtained when following her preferences. Due to this fact financial incentives are useful in exceptional cases only. Social incentives, on the other hand, require a lower investment non-electricity related that may represent a higher subjective benefit for some users, who will decide to collaborate to the proposed demand response program because the gained profit of the complimentary proposal that accompanies the demand response program. For instance, a feasible incentive could be the destination of some amount of resources for natural reserves funding and reforestation, with the quantity being proportional to the electricity consumption changes for required periods. In this case, users concerned about the environment will be willing to collaborate as they will perceive a higher benefit, even if it is not a monetary income or bill reduction, thus, they will shift their preferences. The choice of whether accepting or not a specific demand response program and users' subjective valuation given to the energy usage are modeled using opinion dynamics, where users form a social network in which the opinion evolution due to users' influence is calculated until the system reaches a stable state. Energy valuation of each user is weighted by her opinion, such that the final choice of enrollment in a management program depends on a probability given by the user's opinion. In a general case, the model allows to estimate the effectiveness of a certain social incentives program, once its initial acceptance within the population is known.